2009
DOI: 10.1016/j.ijgo.2009.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Preterm delivery and ultrasound measurement of cervical length in Gran Canaria, Spain

Abstract: Transvaginal measurement of cervical length during routine fetal morphological examination between the 18th and 22nd week of pregnancy helps identify asymptomatic women at risk for preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…10 In yet another study by Barber et al, the specificity, sensitivity, positive and negative predictive values of cervical length for assessing preterm birth was reported as 98%, 26%, , 63.6%, 93.57% respectively, which was slightly lower than that of our study. 11 In a study by Lim et al transvaginal ultrasound for the measurement of cervical length was reported to be a very effective, safe and acceptable technique in predicting the preterm birth. Cervical length was reported to be inversely related to the risk of preterm birth in asymptomatic women.…”
Section: Discussionmentioning
confidence: 99%
“…10 In yet another study by Barber et al, the specificity, sensitivity, positive and negative predictive values of cervical length for assessing preterm birth was reported as 98%, 26%, , 63.6%, 93.57% respectively, which was slightly lower than that of our study. 11 In a study by Lim et al transvaginal ultrasound for the measurement of cervical length was reported to be a very effective, safe and acceptable technique in predicting the preterm birth. Cervical length was reported to be inversely related to the risk of preterm birth in asymptomatic women.…”
Section: Discussionmentioning
confidence: 99%
“…18 A total of 184 deliveries (7.2%) occurred before the 37th week. Before the 37th week, the odds ratios (ORs) of spontaneous delivery for cervical lengths in the 3rd, 5th, and 10th percentiles were, respectively, 25.47 (95% confidence interval [CI], 15.5-41.73); 16.98 (95% CI, 11.51-25.05); and 7.55 (95% CI, 5.44-10.5).…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal morbidity and mortality are mostly caused by preterm delivery. 1,2 Basically, the exact mechanism behind preterm labor was not yet known clearly. However preterm deliveries may cause decidual hemorrhage, cervical incompetence, Mullerian duct abnormalities, fibroid uterus, cervical inflammation, hormonal changes, and uteroplacental insufficiency.…”
Section: Introductionmentioning
confidence: 99%